The reactions of Latin American youth to juvenicide - Lerchundi, Mariana (2025)
The article takes up a classic question, but places it in the context of Latin American juvenicide today: how do some youngpeople react to what society is doing to them? It is assumed that young people have agency, that they do not behave as mere passive subjects in the face of the different markers of juvenicide. To answer the initial question, interviews and workshops on violence conducted with young people in Argentina, Colombia and Costa Rica will be analyzed, alluding to three central markersof juvenicide: institutional-police violence, neighborhood violence and sociocultural violence.